Polemik Pemberitaan Hasil Tes Wawasan Kebangsaan yang Menonaktifkan 75 Pegawai KPK (Analisis Framing pada Media Online Kompas.com dan Antaranews.com - Yulia Rahmawati; yenrizal yenrizal; Ahmad Muhaimin (Program Studi Ilmu Komunikasi Fakultas Ilmu Sosial dan Politik Universitas Islam Negeri Raden Fatah Palembang, 2022)
On May 6, 2021, the announcement of the Tes Wawasan Kebangsaan (TWK) results for employees of the Komisi Pemberantasan Korupsi (KPK) generated mixed reactions in the community, as 75 employees of the anti-corruption institution were declared not to be to have passed the TWK. Several prominent figures were holding large mattresses among the 75 names of employees who did not pass. This study examines two Indonesian online news portals, Kompas.com and Antaranews.com. This study aims to examine how the media frames and compares the results of the TWK of KPK employees. This study takes a qualitative approach, collecting data through observation and conducting a literature review using Robert N. Entman's framing analysis model. The purpose of this research is to write a news article about the controversy surrounding the TWK results for KPK employees for the period June 17–18, 2021. The findings of this study demonstrate that there are differences in how the online news portals Kompas.com and Antaranews.com frame the news regarding the polemics surrounding the National Insight Test results for KPK employees. Kompas.com frequently frames news negatively, implying that the KPK will manipulate and wash their hands of the TWK case. Meanwhile, Antaranews.com developed the framing as KPK clarification news, i.e., a guarantee regarding the originator of the TWK concept. Keywords: Framing Analysis, TWK KPK staff, Kompas.com and Antaranews.com